Assessment of the epidemiological risk factors of diabetic and hypertensive patients amongst the adult population - K. B., Suryananth; J. S. Meena; Manju Toppo; Devendra Gour (International Journal Of Community Medicine And Public Health, 2024)
Background: 93 lakh people in India are undergoing diabetes and hypertension medication. It is true that the most important modifiable risk factors for type 2 diabetes and hypertension today are poor diet, cigarette smoking, and insufficient exercise. NCD-related deaths worldwide will increase by 17% by 2025, costing 47 trillion in lost productivity between 2011 and 2030. Methods: 300 diabetics, hypertensive and diabetic with hypertensive patients were selected from 8 urban wards and 8 rural panchayats of Bhopal by multi-stage random sampling. A semi-structured, pretested and validated questionnaire derived from WHO-STEPS survey was used to collect data in terms of socio-demographic variables, behavioural risk factors measurement and physical measurements. Mean and standard deviations were calculated for quantitative data, frequency and proportions were calculated for qualitative data. Chi-square value was calculated and p value less than 0.05 was considered statistically significant. Results: The mean age was 46.55±2.17 years. DBP found to be 3% more than 39% of males have systolic BP ≥140 mm of Hg. 33.6% fall under obese-I category. Current tobacco smokers, current alcohol consumption, heavy alcohol use, salt intake >5 gm/day, BMI ≥30 (obese-II) was significantly associated with hypertension. Conclusions: The study’s findings indicate that the alarmingly high occurrence of risk factors for diabetes and hypertension among adults need immediate attention. This indicates the need for an extensive screening and awareness campaign to identify undetected cases in the community and to offer early treatment and continuous follow-up to prevent consequences.